PENGARUH RELIGIUSITAS DAN LITERASI KEUANGAN SYARIAH TERHADAP MINAT MENABUNG DI BANK SYARIAH INDONESIA (BSI) PADA MAHASISWA EKONOMI SYARIAH (IAI Nasional Laa Roiba Bogor) - Santi; Toni Endaryono, Bakti; Prasetyo, Agung; Abdilah Kurniawan, Luluh (Jurnal Gici Jurnal Keuangan dan Bisnis, 2023)
The purpose of this study is to discuss and determine the influence of religiosity and Indonesian Sharia financial literacy (BSI) on IAI Nasional Sharia economics students Laa Roiba Bogor. This research method uses a descriptive method with a quantitative approach with as many as 161 students with Regression analysis tools, The data collection technique used is by direct observation by making observations at the Sharia Economics Study Program of IAI Nasional Laa Roiba Bogor. The results of the study were found that (1) Religiosity had a positive and significant effect on Student Saving Interest, (2) Islamic Financial Literacy had a positive and significant effect on Student Saving Interest, (3) There was a simultaneous influence between Religiosity (X1) and Islamic Financial Literacy (X2) with Regression obtained the value of the coefficient of determination (R2) of the independent variable with the dependent variable was 0.758 (75.8%), This means that the amount of contribution of the independent variable to the dependent variable is 75.8% and the remaining 24.2% (100% - 75.8% = 24.2% comes from other variables or factors that have not been studied in this study. Based on the Model Summary table, the value of relationship strength (R) is obtained.